(untitled) (Geographical Journal of Nepal, 2017)
For the empowerment of women several international meetings, conferences and seminars have been taking place globally. Consequently, women are becoming stronger in social, economic, and political sectors. The numbers of women state heads have revealed that internationally women are being empowered politically. Women’s struggle in Nepal has also brought a remarkable change in establishing women rights in social, economic, and political spheres. After democratic restoration, few efforts have been made for their empowerment. Still the Human Development index of women is not so encouraging. However, they have been involved in multi sectoral activities such as household economy, environmental conservation, social functions, and infrastructure development. After 1990, political parties have involved women in their political organizations and have provided opportunities to be elected and nominated in the national legislature, executive and judiciary. Few of them have already got chances to be Minister and Member of Parliament.Similarly, women have been working as District Development or Village Development Committee chairperson. In the inaccessible remote areas still they are not much empowered and their involvement is less. It is necessary to make them empowered.